Pengaruh Model Pembelajaran Radec (Read, Answer, Discuss, Explain, Create) Terhadap Kemampuan Berpikir Kritis Siswa Pada Mata Pelajaran Bahasa Indonesia Kelas V Sd It Salsabila Palembang - Rahmawati, Novia; Murniviyanti, Liza; Riyanti, Henni (Indonesian Journal of Islamic Elementary Education, 2024)
Learning explanatory text material requires a model that is in accordance with the education system in Indonesia which requires students to understand many scientific concepts with limited time. This study aims to determine whether there is an Effect of the RADEC Learning Model (Read, Answer, Discuss, Explain, Create) on Students' Critical Thinking Skills in the Indonesian Language Subject of Class V of SD IT Salsabila Palembang. This study uses a quasi-experimental research design with a measurement technique using pretest and posttest. The population in this study were all students of class V of SD IT Salsabila Palembang. The sample in this study was class V Baghdad as the control class, and class V Jeddah as the experimental class. The data collection technique used in this research activity was test and documentation. The data analysis technique used was the independent samples t-test. In the results of the pretest and posttest in the control class and in the experimental class which showed a significant difference after applying the RADEC learning model, the data analysis obtained was 0.041 <0.05 then Ho was rejected and Ha was accepted. So it can be concluded that there is an effect of the RADEC learning model on students' critical thinking skills.